Employing Peter Newmark's Approaches to Language Transfer to Study English-Vietnamese Translation of Metaphors and Similes (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The seven procedures proposed by Peter Newmark for translating metaphors, and, by expansion, for translating similes have become an almost undisputable theoretical foundation for the translation of this type of figure of speech. However, his proposal was made in the context of cultural overlap and applicable to Indo-European languages which are lexically and syntactically related. This study, based on the topic-illustration-point of similarity model of semantic analysis, carried out an investigation into translating metaphors and similes as seen in contemporary translated works from English into Vietnamese. The procedures for translating metaphors and similes were identified and classified in order of popularity and were then compared with those suggested by Newmark which were arranged in order of preference. The research findings include different tendencies in adopting a procedure for translating metaphors and similes from English into Vietnamese in translated works and between English and those European languages in Newmark’s studies. The research also puts forward some recommendation in relations to implications on translating and on language teaching and learning.